PHYSICAL CHARACTERISTICS OF ACTIVE MUSCLE BALI BEEF GIVES THAT GIVEN ADDITIONAL FEED AND GROWTH PROMOTORS - Suryanadi, Ni Wayan; Swacita, Ida Bagus Ngurah; Suwiti, Ni Ketut (Buletin Veteriner Udayana; Vol. 14 No. 4 August 2022, 2022)
Meat is one of the agricultural commodities needed to meet protein needs, because meat contains high quality protein and contains complete essential amino acids. To increase the amount of meat, breeders provide feed additive and growth promoters. Therefore, it is necessary to conduct research on its effect on meat quality, especially meat derived from active muscles. Experimental research was conducted using a completely randomized design factorial pattern, using 24 male Bali cows aged 18 months and divided into 4 treatments, namely G0P0 / control not injected with growth promoter and without additional feed. G0P1, growth promoter is not injected but given additional feed. G1P0 was injected with the growth promoters without additional feed and G1P1 was injected with the growth promoter and given additional feed. The study was conducted for six months, and at the end of the study, 500 grams of meat samples were taken each. Measurement of water holding capacity, pH and cooking losses were carried out following the method of Joo et al. (2013). The results showed that the provision of growth promoter and additional feed had no effect on pH and water binding capacity, but the combination of treatments reduced Bali beef cooking losses. From the provision of additional feed with growth promoters can provide quality Bali beef which can be reviewed based on the location of active muscles.